Analisis Fundamental Makro, Fundamental Mikro Terhadap Nilai Perusahaan dengan Struktur Kepemilikan, Manajemen Laba dan Kinerja Keuangan sebagai Variabel Moderasi pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2019-2023 - Rahayu, Putri; Hwihanus (LANCAH: Jurnal Inovasi dan Tren, 2024)
This research focuses on firm value as an important component in the business world that shows financial and operational strength and reputation in the market. The value of the company is very important not only based on the large amount of money, but also how people such as investors, customers, employees and business partners see it. the main indicators for analyzing company value are Price Ealrning Ratio (PER), Price to Book Vallue (PBV). This study highlights several variables that affect the dependent variable (Y), namely firm value. This study uses quantitative methods by analyzing data from the financial statements of companies listed on the Indonesia Stock Exchange. Factors such as Macro Fundamentals, Micro Fundamentals, Ownership Structure, Earnings Management, and Financial Performance are expected to have a significant influence on firm value in the food and beverage sector